Aging of plasma-activated copper and gold surfaces and its hydrophilic recovery after water immersion - Prysiazhnyi, Vadym; Slavicek, Pavel; Cernak, Mirko (Elsevier B.V., 2014)
A significant increase of surface hydrophilicity of copper and gold surfaces was obtained after atmospheric pressure plasma treatment using the surface dielectric barrier discharge with specific electrode geometry, the so-called diffuse coplanar surface barrier discharge. Surface wettability was estimated using the sessile drop method with further calculation of the surface free energy. After the plasma treatments, it was observed that the treated surfaces exhibited hydrophobic recovery (or aging effect). The aging effect was studied in different storage environments, such as air, low and high vacuum. The role of plasma and the reasons of the following aging effect are discussed with respect to the observed hydrophilic recovery after immersing the aged surfaces into deionized water. The changes in the surface morphology, composition and bond structure are presented and discussed as well. (C) 2013 Elsevier B. V. All rights reserved.
Keywords: Plasma treatment; Metal surface; Copper; Gold; Diffuse coplanar surface barrier discharge; Aging effect; Thin films